ChemInform Abstract: β‐Functionalization of Carboxylic Anhydrides with β‐Alkyl Substituents Through Carbene Organocatalysis. Issue 18 (May 2015) - Jin, Zhichao; Chen, Shaojin; Wang, Yuhuang; Zheng, Pengcheng; Yang, Song; Chi, Yonggui Robin
Abstract The first NHC‐catalyzed reaction of aliphatic carboxylic acid anhydrides (I) and (IV) with diones (II) and (V), as well as chalcones (VII), and isatins (IX) is presented to give substituted cyclopentenes (III), (VI), (VIII), and spirocyclic butyrolactones (X).